Invasive disease caused by Streptococcus pneumoniane resistant to penicillin and third-generation cephalosporins - Kularatne, Ranmini Sumudita (My University, 2014)
Resistance to penicillin G and third-generation cephalosporins among Streptococcus pneum oniae is an emerging and increasing microbial threat. Over a AVi year study period, w e identified 4 0 patients with either intermediate (26/40, 65%) or high-level (14/40, 35%) resistance to third-generation cephalosporins (i.e., ceftriaxone and cefotaxime). Fifteen subjects were adults (mean age 47 years) and 25 were children (mean age 26.5 months). Study isolates were recovered from the follow ing body sites: blood (25 isolates); CSF (5); sputum (5); tracheal aspirates (4); eye socket swabs (4); bronchial washings (1); and ascitic fluid (1). Sites o f primary pneumococcal infection were: pneumonia (26 cases); meningitis (5); skin and soft tissue (post-enucleation for retinoblastoma)(4 ); primary bacteremia (4); and primary peritonitis (1). Sixty-three percent o f infections were community-acquired and 37% were nosocom ial in origin. Thirty-three percent and 29% of subjects with community-acquired and nosocomial infection,respectively, had been hospitalized within the three months prior to pneumococcal infection. Overall, one third o f patients had. received prior antibiotic therapy. HTV/AIDS was the m ost common underlying condition for both adults and children. Overall mortal!uy was 10.5% (4/38 patients), all were fem ale adults with poor prognostic features including severe underlying illness, advanced age, nosocomial pneumococcal infection, and multilobar pneumonia. O f the three patients with both clinical and m icrobiological evidence of meningitis, two received appropriate combination therapy and recovered; one patient receiving ceftriaxone alone died. All study isolates were contained within .'if current 23-polyvalent vaccine, and 84% o f patients were vaccine candidates. More accurate survcillanr. ■ ' cephalosporin resistance among pneumococci is needed including routine screening o f clinically sig iu f "a«t isolates. M odification of current empiric treatment guidelines for suspected pneumococcal meningitis may be necessary based upon local, regional, and national prevalences o f cephalosporin resistance.